Implementasi Budaya (Kebiasaan) Warga Sekolah SMA Antartika Sidoarjo di Dasari Dengan Visi, Misi, dan Tujuan Sekolah - Subianto Karoso; Yanuartuti, Setyo; Handayani, Enie Wahyuning; Nuriana, Ervin (Journal of Practice Learning and Educational Development, 2023)
School culture is a complex concept. Generally, culture can be defined as a way of life that develops within a community and is passed down from generation to generation. School culture encompasses various elements such as language, religion, customs, arts, and social norms that shape the identity of a group. The school environment possesses a unique culture, as each school has its own profile based on its characteristics. Cultural education is the knowledge imparted to students based on existing culture, including cultural values, norms, and skills in the field of culture. The essence of culture is a system of values, norms, and regulations that persist within a group.In many schools, habitual activities such as commemorating national holidays help students become more active and participatory in school activities. Exemplary behaviors such as dressing neatly, arriving on time, and communicating politely enable students to internalize desired behaviors in their daily lives. School culture plays an important role in shaping character. As educational institutions, schools have visions, missions, and goals not only to disseminate knowledge but also to cultivate the morals and behaviors of students through the values taught within the school environment.By implementing positive culture, students are expected to develop good character, become responsible individuals, and contribute positively to society. Therefore, it is essential for every school to develop a culture that supports character education and creates an inclusive and productive learning environment. Thus, school culture not only shapes students' character to be more disciplined and independent but also creates a stable and structured learning environment within the school.